Flights of Minds: Adhering to the Recent Migration of Educated Youth and Its Impact on Pakistan's Future - Sayed, Muaaz; Raja, Maryam; Mehak, Sakeena (The Lighthouse Journal of Social Sciences, 2024)
The phenomenon known as "brain drain," which refers to the departure of highly educated and talented individuals from developing countries like Pakistan, is a regrettable but unavoidable reality. A multitude of variables, both pull and push, contribute to the phenomenon of brain drain. These causes include a lack of employment opportunities, higher income, improved living standards, access to cutting-edge technology, and political conditions that are more stable in industrialized nations like the United States. The expansion of a nation's industrial sector is hampered when there is a shortage of skilled and educated workers, which in turn slows down the overall development of the country. The editorial viewpoint dives deeply into the subject of brain drain, discussing its causes, the repercussions of its disappearance, and the potential solutions to the problem. The perspective of the study emphasizes the significance of appropriate legislative actions as a means of combating the problem and transforming the loss of brainpower into an increase in wisdom. Management needs to take part in preventing the loss of intellectual capital to ensure sustained economic growth and development. To solve the issue, management may be able to assist in addressing it by engaging with the government and other stakeholders, investing in research and development, developing returnee programs, addressing sociocultural factors, and attracting and keeping competent workers. The unfortunate phenomenon of brain drain is something that Pakistani politicians, academics, and other individuals need to address quickly. Pakistan can achieve its long-term economic development goals by attracting and keeping brilliant individuals, as well as by minimizing the causes that lead to brain drain.